Genetic Variants Associated With Sudden Cardiac Death in Victims With Single Vessel Coronary Artery Disease and Left Ventricular Hypertrophy With or Without Fibrosis - Vähätalo, Juha H.; Holmström, Lauri T. A.; Pylkäs, Katri; Skarp, Sini; Porvari, Katja; Pakanen, Lasse; Kaikkonen, Kari S.; Perkiömäki, Juha S.; Kerkelä, Risto; Huikuri, Heikki V.; Myerburg, Robert J.; Junttila, M. Juhani (Frontiers in Cardiovascular Medicine, 2022)
Objective: Cardiac hypertrophy with varying degrees of myocardial fibrosis is commonly associated with coronary artery disease (CAD) related sudden cardiac death (SCD), especially in young victims among whom patterns of coronary artery lesions do not entirely appear to explain the cause of SCD. Our aim was to study the genetic background of hypertrophy, with or without fibrosis, among ischemic SCD victims with single vessel CAD. Methods: The study population was derived from the Fingesture study, consisting of all autopsy-verified SCDs in Northern Finland between the years 1998 and 2017 (n=5,869). We carried out targeted next-generation sequencing using a panel of 174 genes associated with myocardial structure and ion channel function in 95 ischemic-SCD victims (mean age 63.6±10.3 years; 88.4% males) with single-vessel CAD in the absence of previously diagnosed CAD and cardiac hypertrophy with or without myocardial fibrosis at autopsy. Results: A total of 43 rare variants were detected in 43 subjects (45.3 %). Five variants in 8 subjects (8.4%) were classified as pathogenic or likely pathogenic. We observed 38 variants of uncertain significance in 39 subjects (40.6 %). Variants were detected in myocardial structure protein coding genes, associated with arrhythmogenic right ventricular, dilated, hypertrophic and left ventricular non-compaction cardiomyopathies. Also, variants were detected in RYR2, a gene associated with both cardiomyopathies and catecholaminergic polymorphic ventricular tachycardias. Conclusions: Rare variants associated with cardiomyopathies, in the absence of anatomic evidence of the specific inherited cardiomyopathies, were common findings among CAD-related SCD victims with single vessel disease and myocardial hypertrophy found at autopsies, suggesting that these variants may modulate the risk for fatal arrhythmias and SCD in ischemic disease.